Idem prema ipse: performativ pripovjednog identiteta u Na rubu pameti i Jedan, nijedan i sto tisuća - Čale, Morana (2007)
Idem against Ipse: the Performance of Narrative Identity in Pirandello’ s Uno, nessuno e centomila and Krleža’ s Na rubu pameti Articulating the interdependence between narration and the constitution of personal identity in structurally homologous ways, Pirandello’ s Uno, nessuno e centomila (One, No One, and One Hundred Thousand, 1925) and Krleža’ s Na rubu pameti (On the Edge of Reason, 1938) could be taken to substantiate Ricœ ur’ s claim that fiction is a laboratory where the potentials of narrative identity are being tested. In both cases, the plot revolves around a break which seems to have occurred within the previous, presumably coherent, identity of the respective main characters, but which is also the foundational event of their birth to narration, both as narrative characters and as autodiegetic narrators. The &laquo ; semic configurations&raquo ; (Barthes) of the self-narrating subjects are predicated upon the acknowledgment of the gap between their appearance as &laquo ; heteronomically&raquo ; determined (Žmegač) persons and their ungraspable inner selves, the latter being suddenly perceived as obliterated by the former. The two aspects of personal identity, which constitute an ethical-ontological, as well as an autobiographical split, correspond to what Ricœ ur defines as the numerical identity of uniqueness, continuity, and permanence of structural properties allowing for successive re-identifications, or idem-identity (m&ecirc ; meté) ; and the reflexive relation to one’ s own self, implying responsibility towards the other, or ipse-identity (ipséité). The autodiegetical narrators provide an account of their characters’ efforts to recover their ipseities, shattered as these are not only by the inevitable exposure of the subject to the violence of the other’ s gaze, but also by their own mechanical conformity to normalcy. Violence breeds violence: by deciding to destroy its double, the self forfeits the possibility of its own self-reflexive action. The self claiming its rights is revealed to be a construction of the narrative discourse, which, for its part, displays the improbable realisation of the literary text’ s ipseity, i.e. of its meaning beyond the surface of its illusionary referentiality.
Projekt MZOS
HRV